Bottom-up approach to build osteon-like structure by cell-laden photocrosslinkable hydrogel - Zuo, Yicong; Xiao, Wenqian; Chen, Xiaoqin; Tang, Yajun; Luo, Hongrong; Fan, Hongsong (Chemical communications (Cambridge, England), 2012)
Based on photocrosslinkable PEGDMA and GelMA hydrogels, two "bottom-up" approaches ("circle-and-cross" and "layer-by-layer") were successfully developed to construct osteon-like structures with microchannel networks. Significantly, the "layer-by-layer" approach employing the GelMA hydrogel with a higher biocompatibility was more favorable for building biomimetic osteon.